Identifying the Potential Causes, Consequences, and Prevention of Communicable Diseases (Including COVID-19). (5th November 2020) - Anser, Muhammad Khalid; Islam, Talat; Khan, Muhammad Azhar; Zaman, Khalid; Nassani, Abdelmohsen A.; Askar, Sameh E.; Abro, Muhammad Moinuddin Qazi; Kabbani, Ahmad
Abstract : Communicable and noncommunicable diseases cause millions of deaths every year, increased billions of healthcare expenditures, and consequently increase trillions of economic losses at a global scale. This study more focused on the prevalence of communicable diseases, including COVID-19 that is an emerging pandemic, which affects the global economy. The objective of the study is to examine the impact of population density, lack of sanitation facilities, chemical concentration, fossil fuel combustions, poverty incidence, and healthcare expenditures on communicable diseases including COVID-19. The study covered a large panel of heterogenous countries to assess the relationships between the stated factors by using the robust least square regression, Granger causality test, and innovation accounting matrix. The study used a time series data from 2010 to 2019 for assessing the determinants of communicable diseases, while it is further extended with the current data of 2019-2020 for the COVID-19 pandemic. The results of the study show that high population density, lack of primary handwashing facilities, chemicals used in manufacturing value-added fossil fuel combustion, and poverty headcount substantially increase communicable diseases. In contrast, population diffusion, low carbon concentration in air, renewable fuels, and healthcare expenditures decrease infectious diseases in a panel of 78 countries. The causal inferences found the bidirectional relationship between communicable diseases and primary handwashing facility, and carbon emissions and poverty headcount, whereas the unidirectional relationship is running from lack of sanitation to infectious diseases, economic growth to carbon emissions, and communicable diseases to fossil fuel combustion across countries. Communicable diseases increase healthcare expenditures and decrease the country's economic growth which is a vital concern of the global economy to confront the outbreak of novel coronavirus through increasing the healthcare budget in national bills and stabilize financial activities at a worldwide scale.